Influence of pore size in protein G'-grafted mesoporous silica nanoparticles as a serum pretreatment system for in vitro allergy diagnosis - Paris, Juan Luis; Monío, Cristina; Pérez-Moreno, Ana M.; Jurado-Escobar, Raquel; Bogas Herrera, Gádor; Fernández-Duarte, Tahía Diana; Montañez-Vega, María Isabel; Mayorga Mayorga, Cristobalina; Torres-Jaén, María Josefa (Wiley, 2023)
Particles with the capacity to bind to immunoglobulin G (IgG) can be used for the purification of IgG or to process clinical samples for diagnostic purposes. For in vitro allergy diagnosis, the high IgG levels in serum can interfere with the detection of allergen-specific IgE, the main diagnostic biomarker. Although commercially available, current materials present a low IgG capture capacity at large IgG concentrations or require complex protocols, preventing their use in the clinic. In this work, mesoporous silica nanoparticles are prepared with different pore sizes, to which IgG-binding protein G’ is grafted. It is found that for one particular optimal pore size, the IgG capture capacity of the material is greatly enhanced. The capacity of this material to efficiently capture human IgG in a selective way (compared to IgE) is demonstrated in both solutions of known IgG concentrations as well as in complex samples, like serum, from healthy controls and allergic patients using a simple and fast incubation protocol. Interestingly, IgG removal using the best-performing material enhances in vitro IgE detection in sera from patients allergic to amoxicillin. These results highlight the great translation potential of this strategy to the clinic in the context of in vitro allergy diagnosis.
Keywords: Alergia-Diagnóstico; Allergies; Immunoglobulin; In vitro diagnostics; Mesoporous silica nanoparticles